2023
DOI: 10.1002/aenm.202203540
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Organic Framework Based Lithium–Sulfur Batteries: Materials, Interfaces, and Solid‐State Electrolytes

Abstract: Lithium–sulfur batteries are recognized as one of the most promising next‐generation energy‐storage technologies owing to their high energy density and low cost. Nevertheless, the shuttle effect of polysulfide intermediates and the formation of lithium dendrites are the principal reasons that restrict the practical adoption of current Li–S batteries. Adjustable frameworks, structural variety, and functional adaptability of covalent organic frameworks (COFs) have the potential to overcome the issues associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(64 citation statements)
references
References 189 publications
0
64
0
Order By: Relevance
“…Accordingly, among the various candidates, lithiumsulfur (Li-S) batteries have attracted extensive attention in the last few decades because of their numerous advantages, such as extremely high theoretical capacity (sulfur: 1675 mAh g −1 ), energy density (2600 Wh kg −1 ), low cost, abundance, and environmental friendliness. [4][5][6][7][8][9][10][11][12] Despite these advantages, realizing the practical application of Li-S batteries remains a great challenge. In particular, S cathodes suffer from some severe problems.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, among the various candidates, lithiumsulfur (Li-S) batteries have attracted extensive attention in the last few decades because of their numerous advantages, such as extremely high theoretical capacity (sulfur: 1675 mAh g −1 ), energy density (2600 Wh kg −1 ), low cost, abundance, and environmental friendliness. [4][5][6][7][8][9][10][11][12] Despite these advantages, realizing the practical application of Li-S batteries remains a great challenge. In particular, S cathodes suffer from some severe problems.…”
Section: Introductionmentioning
confidence: 99%
“…17,26 Moreover, the application of polymers and 2D porous materials in gel/SSEs and other areas was also presented, and thus it is expected that more effort will be devoted to the development of FOMs in rechargeable batteries. 218 However, most of the previous studies on FOMs have focused on improving the metal interface, especially in Li metal batteries. 14,21,101,133 They also appeared in the anodic protection of Na, K, Zn, and Mg metal batteries, but the studies are still in their infancy.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…Notably, COFs with tunable structure, thermal stability, and low density have become alternative candidates. 218 Yang et al designed an excellent self-supporting TPB-BD(OH) 2 -COF/PVDF separator, which could induce the uniform distribution of Li + and greatly inhibit dendrite growth. 219 COFs with hydroxyl functional groups will interact with the electrolyte components to form a hydrogen bond network, showing a good desolvation effect and limited side reactions in the resultant separator.…”
Section: Advances In Foms Used As Protection Layers In Secondary Meta...mentioning
confidence: 99%
“…The Applications of COFs as separators in LSBs are as widespread as MOFs due to their merits of the diverse structure, high porosity and functional groups. [111] In 2016, Y et al reported a microporous COF net on a mesoporous CNT)net to chemically trap the polysulfides. [112] The two special COFs with different micropore sizes (COF-1 (0.7 nm) and COF-5 (2.7 nm)) have proved the effect of the pore size and the adsorption phenomena of polysulfides by density functional theory calculations (Figure 6e).…”
Section: Lithium-sulfur Batteriesmentioning
confidence: 99%